1998
DOI: 10.1088/0953-4075/31/19/009
|View full text |Cite
|
Sign up to set email alerts
|

Triple differential cross section measurements in H2and D2

Abstract: Triple differential cross sections (TDCS) for double photoionization in H2 and D2 (for comparison also in helium) have been measured for equal energy sharing, E 1 = E 2 = 10 eV. In agreement with previous observations by the Reddish group and in comparison to the equivalent helium case, our D2 data confirm a `narrowing' effect in the correlation factor which influences the observed TDCS lobes, as well as a `filling-in' effect at relative angles θ1,2 = 180°. However, we do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 12 publications
3
27
0
Order By: Relevance
“…When integrated over the momentum of an undetected electron for comparison with the ion-electron results of Dörner et al (1998b), we obtain the azimuthally symmetric electron distribution they observed for ion-axis alignments both parallel and perpendicular to the photon polarization axis. When integrated over the alignment of an undetected ion axis for comparison with our (γ, 2e) data and also the data of Scherer et al (1998), we obtain an expression with two contributions: one identical in form to the helium TDCS; and one with an angular distribution independent of the photon polarization direction and proportional to the square of the difference in amplitudes for parallel and perpendicular molecular excitation. The result is in good agreement with measured ratios of the TDCS in D 2 to that in He and helps to explain a surprising observed increase in the ratios where the individual angular distributions vanish due to an exact parity-exchange selection rule.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…When integrated over the momentum of an undetected electron for comparison with the ion-electron results of Dörner et al (1998b), we obtain the azimuthally symmetric electron distribution they observed for ion-axis alignments both parallel and perpendicular to the photon polarization axis. When integrated over the alignment of an undetected ion axis for comparison with our (γ, 2e) data and also the data of Scherer et al (1998), we obtain an expression with two contributions: one identical in form to the helium TDCS; and one with an angular distribution independent of the photon polarization direction and proportional to the square of the difference in amplitudes for parallel and perpendicular molecular excitation. The result is in good agreement with measured ratios of the TDCS in D 2 to that in He and helps to explain a surprising observed increase in the ratios where the individual angular distributions vanish due to an exact parity-exchange selection rule.…”
Section: Introductionmentioning
confidence: 69%
“…A thorough study of the resulting few-body escape dynamics clearly requires measurement of differential cross sections, particularly for the lowest photon energies. Recent (γ, 2e) studies of D 2 (Reddish et al 1997a, Wightman et al 1998, Scherer et al 1998 have demonstrated a remarkable likeness of D 2 and helium triply differential cross sections (TDCS), although the characteristic pair of lobes in the helium distributions are closer together in the molecule and significantly narrower. The two groups' measurements are in excellent agreement and were both obtained for equal electron energy sharing, E 1 = E 2 ∼ 10 eV, with coplanar detection orthogonal to the photon beam direction.…”
Section: Introductionmentioning
confidence: 99%
“…A limited consideration has also been given to the case of n electrons emerging in the field of an ion [6]. However, the case where the particles are of mixed character, as in the case of photofragmentation of molecules has not been treated so far, even though there are now full fragmentation coincidence measurements on the simplest molecules H 2 , D 2 and HD [2][3][4]7]. These cases will be considered here, with particular emphasis on the role played by the identity or otherwise of the nuclei.…”
mentioning
confidence: 99%
“…In these kinematically complete, four-body fragmentation experiments, a strong dependence of the photoelectron angular distribution on the orientation of the molecular axis was demonstrated. This observation was not possible in earlier measurements on randomly oriented H 2 or D 2 molecules [4][5][6][7], which could be described rather adequately by atomiclike analytical models [8,9] or central-field numerical computations [10,11]. The new set of molecular-orientation-specific DPI measurements gave an impetus to the rapid advancement of theory.…”
Section: Introductionmentioning
confidence: 93%
“…These amplitudes are defined in the molecular frame and correspond to the parallel e R N and perpendicular e ⊥R N orientations of the internuclear axis and polarization vector of light, respectively. This technique was very efficient in its description of the DPI of randomly oriented H 2 molecules [4][5][6]. It was successfully extended to account for recent observations of noncoplanar electronpair, molecular-axis angular distributions [28], where the molecular-orientation effects were particularly stark.…”
Section: Introductionmentioning
confidence: 99%